The contributions of small-scale fisheries to sustainable development - Franz, Nicole; Westlund, Lena; Mills, David; Basurto, Xavier; del Mar Mancha-Cisneros, Maria; Virdin, John W.; Smith, Simon; Simmance, Fiona; Vannuccini, Stefania; Gutierrez, Nicolas; Nico, Gianluigi (Food and Agriculture Organization of the United Nations, 2023)
The infographic provides a snapshot of findings from the Illuminating Hidden Harvests report. The findings from the report, led by FAO, Duke University, and WorldFish, highlight the environmental, economic, nutritional, gender, and governance dimensions of small-scale fisheries globally.